SOSIALISASI PSIKOEDUKASI KELUARGA DALAM MENANGANI ORANG DALAM GANGGUAN JIWA - Elvine Magdayan; Rina Oktaviana (Jurnal Abdimas Bina Bangsa, 2023)
Families caring for people with mental disabilities (ODGJ) face a lot of psychological, economic and social pressure. Therefore, they are not optimal for treating and curing ODGJ. Support for the surrounding community and the health worker's family is very important. This non-profit activity aims to provide counseling to families with ODGJ in the work room of the Cahya Maju Health Center. philanthropy uses the method. Psychoeducation through several action steps including family mental health assessment, counseling, planning, implementation and evaluation of family interventions to care for ODGJ at home. The results of the 16 weeks of community service show that families understand mental disorders and have the skills to manage ODGJ at home. In addition, family members feel cared for and supported by the people around them. The recommendation from this activity is that continuous support is needed from the community and Puskesmas health workers to help ODGJ families reintegrate into community life